TLR4 Agonist Monophosphoryl Lipid A Alleviated Radiation-Induced Intestinal Injury. (3rd June 2019) - Guo, Jiaming; Liu, Zhe; Zhang, Danfeng; Chen, Yuanyuan; Qin, Hongran; Liu, Tingting; Liu, Cong; Cui, Jianguo; Li, Bailong; Yang, Yanyong; Cai, Jianming; Gao, Fu
Abstract : The small intestine is one of the most sensitive organs to irradiation injury, and the development of high effective radioprotectants especially with low toxicity for intestinal radiation sickness is urgently needed. Monophosphoryl lipid A (MPLA) was found to be radioprotective in our previous study, while its effect against the intestinal radiation injury remained unknown. In the present study, we firstly determined the intestinal apoptosis after irradiation injury according to the TUNEL assay. Subsequently, we adopted the immunofluorescence technique to assess the expression levels of different biomarkers including Ki67, γ -H2AX, and defensin 1 in vivo. Additionally, the inflammatory cytokines were detected by RT-PCR. Our data indicated that MPLA could protect the intestine from ionizing radiation (IR) damage through activating TLR4 signal pathway and regulating the inflammatory cytokines. This research shed new light on the protective effect of the novel TLR4 agonist MPLA against intestine detriment induced by IR.